2017
DOI: 10.3892/ol.2017.6099
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus accumbens-1/GADD45GIP1 axis mediates cisplatin resistance through cellular senescence in ovarian cancer

Abstract: Nucleus accumbens-1 (NAC1), a nuclear factor belonging to the bric-a-brac-tramtrack-broad complex/pox virus and zinc finger gene family, is known to serve important roles in the proliferation and growth of tumor cells, and in chemotherapy resistance. However, the underlying molecular mechanisms through which NAC1 contributes to drug resistance remain unclear. In the present study, the role of NAC1 in drug resistance in ovarian cancer was investigated. NAC1 expression was markedly negatively associated with gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…This con rmed the uncontrolled cell proliferation was a core characteristic of OC cells as well as the ovarian cancer stem cells (OVSCSs). In the results of the KEGG pathway, we found that the pathway "Cell cycle" [18,19], "Cellular senescence" [13][14][15], "p53 signaling pathway" [16,17], and "Platinum drug resistance" were closely associated with platinum sensitivity according to previous reports. A recent review had summarized that an insu cient dose of platinum might lead to a cytostatic response, named dormancy, rather than cytotoxic response, through inducing cell cycle arrest and cellular senescence [26].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This con rmed the uncontrolled cell proliferation was a core characteristic of OC cells as well as the ovarian cancer stem cells (OVSCSs). In the results of the KEGG pathway, we found that the pathway "Cell cycle" [18,19], "Cellular senescence" [13][14][15], "p53 signaling pathway" [16,17], and "Platinum drug resistance" were closely associated with platinum sensitivity according to previous reports. A recent review had summarized that an insu cient dose of platinum might lead to a cytostatic response, named dormancy, rather than cytotoxic response, through inducing cell cycle arrest and cellular senescence [26].…”
Section: Discussionsupporting
confidence: 60%
“…These key genes were mainly involved in the pathways of the cell cycle ( Figure 3B). Interestingly, the selected key genes were also enriched to the platinum response-associated pathways "cellular senescence" [13][14][15], "p53 signaling pathway" [16,17], and "Platinum drug resistance" ( Figure 3B). Cell cycle arrest was also the main molecular mechanism of the platinum anticancer effect [18,19].…”
Section: Function Annotation and Pathway Enrichment Of The Selected Kmentioning
confidence: 99%
“…Platinum-based Cisplatin A375, B16F10, B16F10 xenografts SASP, SA-β-gal [64] A2780 SAHF (HP1-γ), morphology, SA-β-gal [68] CNE1 Growth arrest, morphology, SA-β-gal [30] SKOV3, TOV-21G Morphology, SA-β-gal [69] HepG2, SMMC-7721 SA-β-gal, p53, p21 Cip1 , p16 INK4 [70] Follicular lymphoma 3D model SA-β-gal [49] In vivo mouse model (p16-3MR) p16 INK4 [28] Carboplatin H1299, patients' lung tumor samples Cell cycle arrest, SA-β-gal, p16 INK4 , RB, downregulation of cyclin B1 and cyclin D1 [71] Oxaliplatin PROb, CT26 SA-β-gal [72] HepG2, SMMC-7721, patients' colorectal tumor samples SA-β-gal [73] Antimetabolites Methotrexate C85 p53 [74] C85 SA-β-gal [75] MCF-7 SA-β-gal [76] Rat-derived BMSCs and ADSCs SA-β-gal [42] A549 p21 Cip1 , low Ki67, growth arrest, SA-β-gal, increased granularity, morphology, SASP (IL-6, IL-8), γH2AX [43] SH-SY-5Y p21 Cip1 , growth arrest, SA-β-gal, γH2AX [43] HCT116 p21 Cip1 , low Ki67, growth arrest, SA-β-gal, increased granularity, morphology, SASP (IL-8), γH2AX [43] MDA-MB-231 p21 Cip1 , growth arrest, SA-β-gal, morphology, SASP (IL-6, IL-8, VEGF) [43] MCF-7 p21 Cip1 , low Ki67, growth arrest, SA-β-gal, increased granularity, morphology, γH2AX [43] Pemetrexed H1650, A549, H2228, H292, H226 and H1650, A549 xenografts SA-β-gal, morphology, SASP (IL-6, IL-8, IL-1β and MCP-1) [77] A549 SASP, SA-β-gal [78] Gemcitabine Miapaca-2 and Panc-1 SA-β-gal [79] AsPc1, Panc1 SA-β-gal [80] Azacitidine U2OS, MCF7 SA-β-gal, p53, growth arrest [81] TPC-1 SA-β-gal [82] KKU100, HuCCA1, RMCCA1 Morphology, SA-β-gal [83] DU145, LNCaP Morphology, growth arrest, polyploidy [40] Bromodeoxyuridine MNA, STA-NB-10, CLB-Ma mouse xenograft (MYCN-amplified neuroblastoma)…”
Section: Drug Class Drug Name Model/cell Line Senescence Marker Refermentioning
confidence: 99%
“…Cisplatin induces senescence in several melanoma cell lines associated with a vigorous secretory response [64]. Cisplatin also induces senescence in A2780, SKOV3 and TOV-21G ovarian cancer cells; A549 and H292 lung cancer cells; HepG2 and SMMC-7721 hepatocellular cancer cells and CNE1 nasopharyngeal cancer cells [30,[68][69][70]. In addition, carboplatin, a more tolerable cisplatin analogue, was shown to induce senescence in tumor samples obtained from non-small cell lung cancer patients who received carboplatin + docetaxel neoadjuvant therapy [71].…”
Section: Platinum-based Drugsmentioning
confidence: 99%
“…11 NACC1 not only regulates the tumorigenesis and development but also affects the therapeutic effect of chemotherapeutic drugs, causing a chemical resistance. [12][13][14][15] NACC1 knockdown inhibited the cisplatin-induced autophagy, resulting in increased cisplatin cytotoxicity. 13 NAC1 mediates cisplatin resistance by altering the High-mobility group box 1 (HMGB1)mediated autophagic response in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%